Reformulating the Definition of International Arbitral Awards in Indonesia: Responding to Constitutional Court Decision No. 100/2024 and a Comparative Analysis with the Regulation of International Arbitration in Other Countries - Purba, Tesalonika Putri Pinuram Rambe; Amalia, Prita; Trisnamansyah, Purnama (Dinasti Research, 2025)
This article discusses the urgency of reformulating the Definition of International Arbitration Awards as a legal implication following the Constitutional Court Decision No. 100/PUU-XXII/2024 on the implementation of international arbitration awards in Indonesia. The removal of the phrase